2012
DOI: 10.1186/1471-2369-13-112
|View full text |Cite
|
Sign up to set email alerts
|

Care of undocumented-uninsured immigrants in a large urban dialysis unit

Abstract: BackgroundMedical, ethical and financial dilemmas may arise in treating undocumented-uninsured patients with end-stage renal disease (ESRD). Hereby we describe the 10-year experience of treating undocumented-uninsured ESRD patients in a large public dialysis-unit.MethodsWe evaluated the medical files of all the chronic dialysis patients treated at the Tel-Aviv Medical Center between the years 2000–2010. Data for all immigrant patients without documentation and medical insurance were obtained. Clinical data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…Instead, the majority of the women in Eilat and Tel Aviv reported use of facilities that operate outside the regular system of Israeli antenatal services, such as the Terem clinic and the hospital, which are not meant to be the main facility for uptake of antenatal services. Our qualitative data do not provide direct answers to these surprising findings, nor do other studies on Eritrean refugees' utilization of health services reflect on their facility choices for service uptake (Chernin et al, 2012;Michaan et al, 2014;Fleischman et al, 2015;Gebreyesus et al, 2017). Nevertheless, the current research results do suggest that the Israeli system of antenatal care is not completely functional for Eritrean women, so that the women pursue services in facilities outside the regular Israeli antenatal care system.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Instead, the majority of the women in Eilat and Tel Aviv reported use of facilities that operate outside the regular system of Israeli antenatal services, such as the Terem clinic and the hospital, which are not meant to be the main facility for uptake of antenatal services. Our qualitative data do not provide direct answers to these surprising findings, nor do other studies on Eritrean refugees' utilization of health services reflect on their facility choices for service uptake (Chernin et al, 2012;Michaan et al, 2014;Fleischman et al, 2015;Gebreyesus et al, 2017). Nevertheless, the current research results do suggest that the Israeli system of antenatal care is not completely functional for Eritrean women, so that the women pursue services in facilities outside the regular Israeli antenatal care system.…”
Section: Discussioncontrasting
confidence: 64%
“…Chernin et al. () reported similar results for undocumented immigrants’ utilization of health services for end‐stage renal disease, suggesting that frequent utilization of a given service is particularly challenging for Eritrean refugees in Israel. While more experience did not affect the array of services used, frequency rates in the current study were higher for women with more children born in Israel.…”
Section: Discussionmentioning
confidence: 80%
“…The study authors concluded that their data contradict the widely held opinion that people are moving to the USA to receive dialysis treatment 25. An Israeli study showed similar results 26. There are no Canadian data on this issue, and the situation might be different from that in the USA, of Canada's universal health insurance; for example, in France, where there is also universal health insurance, the proportion of FN patients waitlisted for an organ transplant increased between 1996 and 2008 13 16…”
Section: Arguments Regarding Transplantations For Foreign Nationalsmentioning
confidence: 85%
“…Once in the new country, they face multiple barriers in accessing healthcare services (eg, language, lack of knowledge about how the healthcare system works, and about their rights or the resources available to them), may be isolated and without social support, and be stressed about their immigration status 34. This situation can lead FNs to consult late, not receive optimal medical management and thus be in worse health 26. Nonetheless, this vulnerability may be considered insufficient grounds to justify particular attention or care from a host country.…”
Section: Arguments Regarding Transplantations For Foreign Nationalsmentioning
confidence: 99%
“…[17][18][19] Another argument, from a cost perspective, is that many UIs will benefit from preventive care and early treatment of chronic diseases before they advance to lifethreatening and costly complications. 20,21 Proponents of this strategy advocate for improving health literacy and vaccination rates, and offering health screenings to the UI population to try to prevent long-term adverse health outcomes and control cost. Moreover, UIs may harbor infections such as tuberculosis (TB), which, when undetected, can easily be transmitted to the general public, thus posing a public health risk.…”
Section: The National Debate On Medical Care For Undocumented Immigrantsmentioning
confidence: 99%